SPORTMATH LEARNING: PEMBELAJARAN MATEMATIKA KONTEKSTUAL MELALUI AKTIVITAS OLAHRAGA - Mukharrar Fadjri; Nika Fetria Trisnawati; Hidayani Hidayani; Faida Musa’ad; Zakiyah Anwar; La Robi; Albert Anton Mayor (MAJU : Indonesian Journal of Community Empowerment, 2026)
This activity aims to enhance teachers’ competence in applying contextual mathematics instruction through sports activities via the SportMath Learning program. The program is implemented using a participatory and collaborative approach, targeting mathematics teachers and Physical Education, Sports, and Health teachers. The implementation methods include preparation, outreach, workshops and training, practice and simulation, implementation support, and activity evaluation. The learning activities implemented include measuring running speed, calculating game scores, measuring ball throw distance, presenting sports data in the form of tables and diagrams, and applying geometric concepts on the sports field. The results indicate an improvement in teachers’ understanding and skills in designing sports-based mathematics lessons. Additionally, the implementation of SportMath Learning enhances student motivation, participation, and engagement in mathematics learning. This program also fosters an active, enjoyable, and meaningful learning environment for students. The conclusion is that SportMath Learning can serve as an innovative learning alternative that supports the strengthening of numeracy literacy and contextual learning in schools.